PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA PT. JALUR NUGRAHA EKAKURIR CABANG PALOPO - Nirmasari, Dian; Nurwafiyyah, Auliyah; Fadlina, Fadlina (Universitas Ichsan Sidenreng Rappang, 2023)
The problem in this study is whether service quality and price affect customer satisfaction, while the purpose of this study is to determine the effect of service quality and price on customer satisfaction in PT. JNE (Nugraha Ekakurir Line) Palopo. Service quality and price as independent variables , , while customer satisfaction is the dependent variable (Y). The problem in this study is the number of customers who have fluctuated at JNE Palopo, and in the last four years, the target was not achieved only in 2021. The sample for this study was taken from as many as 30 respondents from the population calculated using the Slovin formula. The data was obtained from the questionnaire results and then processed to be tested with statistics through the SPSS 21 program. The results of the tests showed that service quality and price had a positive and significant effect on customer satisfaction at PT. JNE (Nugraha Ekakurir Line) Palopo. The data analysis method used is multiple linear regression analysis.